2003
DOI: 10.1002/pros.10355
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine‐induced neurogenic prostatitis facilitates the promotion of PIN‐like lesions in rats

Abstract: Neuro-immune interactions promote prostatic fibrosis and dysplastic changes; these being preceded by an acute and transient inflammatory reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Previous studies showed that phenylephrine treatment induced atypical prostatic hyperplasia and mild fibrosis in the rat ventral prostate (Golomb et al, 1998;Rosenzweig et al, 2004;Rosenzweig-Bublil and Abramovici, 2006). These effects have been related to a tissue repair process occurring subsequent to the inflammatory exudates that takes place during early period of phenylephrine treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies showed that phenylephrine treatment induced atypical prostatic hyperplasia and mild fibrosis in the rat ventral prostate (Golomb et al, 1998;Rosenzweig et al, 2004;Rosenzweig-Bublil and Abramovici, 2006). These effects have been related to a tissue repair process occurring subsequent to the inflammatory exudates that takes place during early period of phenylephrine treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Growing data displayed the SNS played a role in prostatic disease. Previous reports have shown that continuous exogenic sympathetic stimulation by phenylephrine promotes a biphasic effect on the rat ventral prostate [27] in which a first inflammatory reaction took place at 3-8 h after injection and proliferative changes occurred on the 7th day. Continuous endogenous sympathetic overloading in genetically hypertensive rats was accompanied by spontaneous hyperplasia of the prostate of old rats [28] ; this had also taken place in hypertensive patients [29] .…”
Section: Discussionmentioning
confidence: 99%
“…This effect is cell density-dependent, and the authors focused attention on the role of intercellular communication in coordinating the differentiation pathways. Furthermore, in an animal model, subchronic NA stimulation exerts a biphasic time-related effect on rat ventral prostate: a primary inflammatory response characterized by edema and by large-scale leukocyte infiltration, followed by a secondary proliferative phase involving both the acinar epithelium and the stromal component [51].…”
Section: The Role Of Catecholaminesmentioning
confidence: 99%